Nickel nanoparticles derived from the direct thermal reduction of Ni-containing Ca–Al layered double hydroxides for hydrogen generation via ammonia decomposition. (8th November 2021) - Deng, Lidan; Lin, Huachang; Liu, Xiaowei; Xu, Jie; Zhou, Zijian; Xu, Minghou
Abstract: The fabrication of nanomaterials is a crucial issue in heterogeneous catalysis. Herein, nickel nanoparticles of different particle sizes were derived from the direct thermal reduction of a Ni-containing Ca–Al layered double hydroxide (LDH). Using various characterization methods, such as XRD, TEM, SEM, and TPR-MS, it was found that nickel precursors notably influenced the final morphology of Ni metallic nanoparticles. Ni(NO3 )2 can attend reassembling of reassemble CaAl–NO3 − LDH in water and facilitate the dispersion of Ni in the lamellar structure of the LDH, resulting in the formation of uniform and small Ni metallic nanoparticles (ca.4.7 nm) on CaAlOx via the rapid decomposition of Ni(NO3 )2 in the reduction atmosphere. However, large Ni nanoparticles (ca.14.3 nm) were formed on the CaAlOx catalyst when NiCl2 was used as the precursor and Cl-remained on the final catalyst. The kinetic study and NH3 -TPSR results further indicate that smaller Ni metallic nanoparticles enclosed by CaAlOx exhibited stronger interactions with adsorbed NH3 and facilitated the recombinative desorption of N and H atoms from the catalyst surface. Ni/CaAlOx (NO3 − )-R exhibited the highest activity among the investigated samples. Graphical abstract: Image 1 Highlights: The nickel precursor affects Ni particle size over Ca–Al layered double hydroxide. Ni(NO3 )2 affords much small Ni nanoparticles than NiCl2 . Direct reduction of catalyst precursor induces higher activity than oxidation-reduction. Smaller Ni nanoparticles exhibit stronger interactions with NH3 than bigger ones. Smaller Ni nanoparticles can promote the recombinative desorption of N and H atoms.